A produção textual na sala de apoio à aprendizagem de língua portuguesa : uma análise das condições de produção no Caderno Orientações Pedagógicas - Duarte, Patrícia Cristina de Oliveira (2011)
In the light of Applied Linguistics, this research of qualitative-interpretive basis, aimed to analyze and discuss the process of teaching and learning of text production in Classes that give support to the Learning of Portuguese Language of State of Paraná (SAALP, Portuguese abbreviation). For this, we verified in the section of the text production of the Pedagogic Guideline Booklet, the forms the instruction were presented to produce writing in order to understand, more broadly, the conditions the writing is offered, how the conditions are presented and how the proposals contribute to the formation of a competent text producer, as postulated in the Parâmetros Curriculares Nacionais (BRASIL, 1998) and the Diretrizes Curriculares do Estado do Paraná (Paraná, 2008). The anxieties and concerns that arose from the experience with the textbooks motivated us to undertake this diagnosis. Basing ourselves in the interactionist perspective of language, we concluded that the textbooks already mentioned, disregard the conditions for writing production proposed by Bakhtin/Volochinov (1992), systematized by Gerald (1995), widely held in DCEs (2008) and in the theoretical methodological fundamental of the Pedagogic Guideline Booklet. We observed lack of textual production in SAALP, as thus, the student is not oriented to produce texts "in school", but, yes, "to school". The teaching of writing in SAALP perpetuates the teaching for school writings, as the commands provide a double silence: 1) the closing of discursive possibilities silences the 'saying' of the student because it does not offer him real reasons to justify his utterance, 2) the closing of language possibilities happens because it does not work with the diversity of genres and so it promotes a stereotyping discourse of gender. Thus, the class that should give support to the student serves to bring him difficulty because it does not offer him conditions to acquire good writing skills; on the contrary, the class requires that the student, at all times, should demonstrate communicative competence, a skill that a student of the SAALP does not have.